2018
DOI: 10.1186/s12913-018-3806-2
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Chronic Disease Care System and its association with health care costs and continuity of care in Korean adults with type 2 diabetes mellitus

Abstract: BackgroundThe Chronic Disease Care System (CDCS) has been implemented in Korea to encourage treatment continuity in chronic disease patients. This study investigated the effect of the introduction of the CDCS on health care costs and continuity of care in individuals with type 2 diabetes mellitus (T2DM).MethodsThe National Health Insurance data from August, 2010 to March, 2012 (pre-policy) and from May, 2012 to December, 2013 (post-policy) were used. Introduction of the CDCS was defined as the intervention. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Meanwhile, enhancing continuity of care is important in diabetes management,13 which may require improved access to regional healthcare services. Accessibility to health services can be classified into different dimensions 14.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, enhancing continuity of care is important in diabetes management,13 which may require improved access to regional healthcare services. Accessibility to health services can be classified into different dimensions 14.…”
Section: Introductionmentioning
confidence: 99%
“… 21 A chronic disease care system could improve treatment continuity for adults with type 2 diabetes mellitus. 13 Additionally, Gokalp and Clarke 22 found that most of the existing monitoring systems could provide smart life services such as meal preparation, personal hygiene, bathing, and dressing. These technologies play a pivotal role in improving older adults' daily lives.…”
Section: Discussionmentioning
confidence: 99%
“…A South Korean study confirmed the potential benefits of improving treatment continuity in Korean adults with type 2 diabetes mellitus using a chronic disease care system. 13 Mainstream products with embedded wearable technology and nursing functions, like smart watches and smart phones, provide effective monitoring and alarm systems for the care of older adults, which can mitigate the occurrence of adverse unexpected events such as falls. 14 The application of a remote monitoring system for the management of chronic diseases enabled healthcare providers to conduct remote medical interaction with patients instead of a direct face-to-face medical examination, effectively reducing healthcare costs.…”
mentioning
confidence: 99%
“…Several studies have indicated that improved COC reduces hospitalizations, emergency room visits, medical costs, and risk of death, and increases medication adherence [ 12 17 ]. A previous study on the change in medical care continuity due to a CDMP for diabetic patients confirmed that after participation in the program, medical expenses decreased and treatment continuity increased [ 18 ].…”
Section: Introductionmentioning
confidence: 96%